2004
DOI: 10.2223/jped.1152
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of overweight and obesity in schoolchildren: utilization of the body mass index international standard

Abstract: Objective: To evaluate the agreement between the body mass index international standard and body fat for the diagnosis of overweight and obesity in schoolchildren.Methods: 528 schoolchildren between 6 and 10 years of age, of both sexes, had their weight and height measured. They were then classified as normal, underweight, overweight or obese using the body fat index for age. Body fat was estimated based on the sum of triceps and subscapular, triceps and calf skinfold measurements and waist and hip circumferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
2
7
0
3
Order By: Relevance
“…The present results showing hypertriglyceridemia in about 4% and hypertension + borderline BP in about 12% of the schoolchildren irrespective of gender, agree with most of the data from the Brazilian and international literature (21)(22)(23)(24)(25)(26)(27)(28). However, our data showing that about 1/5 of the students have increased LDL-C represent higher val- Values are correlation coefficients (r ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present results showing hypertriglyceridemia in about 4% and hypertension + borderline BP in about 12% of the schoolchildren irrespective of gender, agree with most of the data from the Brazilian and international literature (21)(22)(23)(24)(25)(26)(27)(28). However, our data showing that about 1/5 of the students have increased LDL-C represent higher val- Values are correlation coefficients (r ).…”
Section: Discussionsupporting
confidence: 91%
“…Since such population studies are relatively scarce in Brazil, the present results can provide important information for the region's public health policy. The overall occurrence of overweight or obesity was about 13.9% for the schoolchildren, a level that, although slightly lower than those reported for the United States (21), Europe (22) and some other regions of Brazil (6,23), suggests that obesity among children is elevated, and might become a public health problem in the Vitória city area. In a study by Guimarães and Guimarães (8) conducted in Salvador, BA, the prevalence of overweight/obesity among 6-12-year-old schoolchildren was similar to that reported here.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…When the results of this study were compared with those of other national and international studies, higher (1,16) and lower (17)(18) percentages are also found. This divergence is not of interest since being overweight might be currently affecting a larger number of individuals earlier in life or is simply related to sampling variations and diagnosis methods.…”
Section: Discussionsupporting
confidence: 55%
“…Sua aferição reflete indiretamente a gordura corporal apendicular (28), e também foi relacionada às mudanças ósseas verificadas em ambos os grupos.…”
Section: Discussionunclassified